Efficacy of Crocus sativus L. on reduction of cadmium‐induced toxicity on spermatogenesis in adult rats. (2nd May 2016) - Yari, A.; Sarveazad, A.; Asadi, E.; Raouf Sarshoori, J.; Babahajian, A.; Amini, N.; Amidi, F.; Bahadoran, H.; Joghataei, MT.; Asadi, MH.; Shams, A.
Summary: Cadmium is a toxic heavy metal element, which probably cause infertility by impairment in spermatogenesis. The present work aimed (i) to study the toxic effect of cadmium on spermatogenesis in rat, as well as (ii) the protective effect of Crocus sativus L. on cadmium‐intoxicated rats. Cadmium chloride was administered intraperitoneally during 16 days at intervals of 48 h between subsequent treatments. Crocus sativus L. was pre‐treated in both of control and cadmium‐injected rats. Animals were sacrificed on day 17 after the first treatment. The left cauda epididymis was removed and immediately immersed into Hank's balanced salt solution for the evaluation of sperm count and viability, and left testis was fixed in 10% formalin for histological evaluation. Following contamination with cadmium, a decrease was observed in the number and viability of cauda epididymis sperm, which were increased by Crocus sativus L. pre‐treatment ( P < 0.05). In addition, cadmium decreased both cell proliferation and Johnsen Scores in the seminiferous tubules, which were reversed by Crocus sativus pre‐treatment ( P < 0.05). Furthermore, cadmium‐induced decrease in the amount of free serum testosterone as well as an increase in lipid peroxidation activity in the testicular tissue was reversed by Crocus sativus L. ( P < 0.05). These findings may support the concept that Crocus sativus L. can improve the cadmium toxicity on spermatogenesis.